2018
DOI: 10.1016/j.rmed.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Qter® and Creatine improves functional performance in COPD patients on long term oxygen therapy

Abstract: These results show that in patients with COPD, dietary supplementation with CoQ10 and Creatine improves functional performance, body composition and perception of dyspnea. A systemic increase in some anti-inflammatory metabolites supports a pathobiological mechanism as a reason for these benefits. Further trials should help clarifying the role of QTer and Creatine supplementation in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 81 publications
0
39
1
2
Order By: Relevance
“…Few clinical trials have been carried out to study the effects of CoQ 10 supplementation as an antioxidant counteracting the oxidative stress in the basis of the disease. DeBenedetto et al demonstrated in a randomized study that 2-months’ supplementation with QTer ® (a formulation for CoQ 10 ) and creatine significantly improved exercise capacity, body composition, dyspnea, and daily activities, and was associated with positive changes in the plasma metabolic profile in COPD patients on long-term oxygen therapy [ 75 ]. However, since the combined use with creatine, it is difficult to attribute all the beneficial outcomes observed by the authors to only the action of QTer ® , mainly the improvement in the exercise capacity and the daily activities, since creatine contribute to a better metabolism in the muscle function.…”
Section: Coq 10 and Chronic Obstructive Pulmonamentioning
confidence: 99%
“…Few clinical trials have been carried out to study the effects of CoQ 10 supplementation as an antioxidant counteracting the oxidative stress in the basis of the disease. DeBenedetto et al demonstrated in a randomized study that 2-months’ supplementation with QTer ® (a formulation for CoQ 10 ) and creatine significantly improved exercise capacity, body composition, dyspnea, and daily activities, and was associated with positive changes in the plasma metabolic profile in COPD patients on long-term oxygen therapy [ 75 ]. However, since the combined use with creatine, it is difficult to attribute all the beneficial outcomes observed by the authors to only the action of QTer ® , mainly the improvement in the exercise capacity and the daily activities, since creatine contribute to a better metabolism in the muscle function.…”
Section: Coq 10 and Chronic Obstructive Pulmonamentioning
confidence: 99%
“…Recently, more attention has been paid to the effects of nutritional supplementation. Researchers have found that compared with the combination treatment of long-term oxygen therapy (LTOT) and placebo, LTOT coupled with nutritional supplementation of CoQ10 and creatine could markedly improve the lung function and symptoms of COPD patients [22]. Metabolites associated with glycerophospholipid and amino acid metabolism had significant differences between the two groups.…”
Section: Copd-associated Biomarkers In Different Sample Types and mentioning
confidence: 99%
“…The main function of creatine is to provide phosphate groups for the conversion from adenosine diphosphate to ATP [102]. Several studies also reported that creatine might protect lung function from oxidative stress damage by reducing superoxide anions and peroxynitrite [22]. The β-oxidation process of long chain fatty acids in the mitochondria depends on the transport of a vital antioxidant, L-carnitine [103].…”
Section: The Role Of Metabolism Dysfunction In Copd Pathogenesismentioning
confidence: 99%
“…Therefore, given its capture of gene function, enzyme activity and physiologic changes, the study of metabolomics has the potential to inform the clinical heterogeneity of COPD phenotypes. While human studies conducted to date have showed that metabolomics analysis of the serum, plasma, urine and exhaled breath condensate can discriminate between never smokers, smokers with COPD and smokers without COPD 711 , the relationship between metabolic profiles and the clinical heterogeneity of COPD has not yet been fully characterized.…”
Section: Introductionmentioning
confidence: 99%